The Soviet Factor in the US-China Military-Technical Cooperation during the Cold War - Yinan Li (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2021)
The development of the PRC’s armed forces included three phases when their modernization was carried out through an active introduction of foreign weapons and technologies. The first and the last of these phases (from 1949 to 1961, and from 1992 till present) received wide attention in both Chinese and Western academic literature, whereas the second one — from 1978 to 1989 —when the PRC actively purchased weapons and technologies from the Western countries remains somewhat understudied. This paper is intended to partially fill this gap. The author examines the logic of the military-technical cooperation between the PRC and the United States in the context of complex interactions within the United States — the USSR — China strategic triangle in the last years of the Cold War. The first section covers early contacts between the PRC and the United States in the security field — from the visit of R. Nixon to China till the inauguration of R. Reagan. The author shows that during this period Washington clearly subordinated the US-Chinese cooperation to the development of the US-Soviet relations out of fear to damage the fragile process of detente. The second section focuses on the evolution of the R. Reagan administration’s approaches regarding arms sales to China in the context of a new round of the Cold War. The Soviet factor significantly influenced the development of the US-Chinese military-technical cooperation during that period, which for both parties acquired not only practical, but, most importantly, political importance. It was their mutual desire to undermine strategic positions of the USSR that allowed these two countries to overcome successfully tensions over the US arms sales to Taiwan. However, this dependence of the US-China military-technical cooperation on the Soviet factor had its downside. As the third section shows, with the Soviet threat fading away, the main incentives for the military-technical cooperation between the PRC and the United States also disappeared. As a result, after the Tiananmen Square protests, this cooperation completely ceased. Thus, the author concludes that the US arms sales to China from the very beginning were conditioned by the dynamics of the Soviet-American relations and Beijing’s willingness to play an active role in the policy of containment. In that regard, the very fact of the US arms sales to China was more important than its practical effect, i.e. this cooperation was of political nature, rather than military one.